Is the White-Collar Worker the Forgotten Man ? - Delaney, Walter (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1954)
SummaryThe "White-Collar" class composed mostly of office workers although not too much known or spoken of constitutes an interesting group in our society, but unfortunately, has not kept pace with the cost of living or wages of plant workers. From this situation serious problems arise which can be studied by the employers themselves; they can be solved if the principles applied to the ordinary worker are also applied, with some little differences, to the clerical worker himself. This is what the author wants to explain briefly in giving some suggestions.